Study of the values ​​of moral education in the ruwatan tradition in Nagrak Village, Ciater District, Subang Regency - Sinta Rohimah, Dede; Komarianti, Cici Siti; Adawiyah, Endah Robiatul; Selvia Ru’yatus Saefullah; Bunga Septria Vionita (Cita konsultindo, 2023)
In this article, the author will describe ruwatan as part of a tradition that is inherent in Nagrak Village, a tradition that is rich in educational values. Ruwatan is often labeled as a negative tradition and tends to be polytheistic. However, this tradition still exists today in the midst of the pros and cons in society. This article tries to explain the positive meaning of Ruwatan and the need to preserve it. Because it contains moral education to educate people to become better human beings. In this case the author raises several problems. Among other things, what are the values ​​contained in the Ruwatan tradition? And how is the implementation of the tradition of ngaruwat earth?. The method that the author uses is a field research method with data collection or observation, interviews and documentation. The sources of data used are scholars, ustadz and community leaders in Nagrak Village who are seen or considered to understand the ngaruwat earth tradition, namely community leaders and books that support the research.